Integrating the 4Cs into EFL Integrated Skills Learning - Pardede, Parlindungan (JET (Journal of English Teaching), 2020)
The accelerative globalization and digitalization in the 21st century have been growingly changing the way we live, interact, learn and work. Consequently, to thrive in the 21st century, besides knowledge and the basic skills, today’s students should also be equipped with what is called the 4Cs (communication, collaboration, critical thinking, and creativity). To meet the challenges, EFL classrooms should not merely focus on students’ language skills development but also integrate the 4Cs into the learning process. This article reviews current ideas and research findings on integrated skills learning, the 4Cs, significance of blended learning in the 4Cs and integrated skills the integration, and offers practical tips for integrating the 4Cs into integrated skills learning.